REINFORCEMENT MERUPAKAN SALAH SATU ALTERNATIF UNTUK MENGURANGI PERILAKU NEGATIF BAGI ANAK TUNALARAS - Fariz Perdana Putra (Universitas Negeri Padang, 2014)
Abstract: This research is motivated by problems found, the children who behave negatively tunalaras said the rough. After a day of observation in school children result rant as much as 5 times. This study aims to reduce negative behavior through negative reinforcement in second grade children in special schools tunalaras Hikmah Miftahul Jannah Padang. The research method used is a Single Subject Research (SSR). This study used a design A-B-A. A condition in which the (baseline) is the initial condition before the child is given the action. Condition B (intervention) in which treatment is given through negative reinforcement. While the condition A is the initial condition after the intervention is no longer given. The results of research that says a rough child behavior decreased after the intervention administered through negative reinforcement. In the baseline condition performed eight times the lowest frequency of observations obtained is 4, the intervention condition performed eight times observations say rude behavior where the child goes down the lowest frequency is 2, the baseline condition (A2) conducted behavioral observations say five times the lowest frequency is coarse 2. Thus the proposed problem formulation proved missed that say rude behavior can be reduced through negative reinforcement in second grade children in special schools tunalaras Hikmah Miftahul Jannah Padang. Researchers suggest to the teacher that uses negative reinforcement to reduce behavior say rude. Kata-kata kunci : reinforcement negatif; perilaku negatif; anak tunalaras